Infection with a Brazilian isolate of Zika virus generates RIG‐I stimulatory RNA and the viral NS5 protein blocks type I IFN induction and signaling. Issue 7 (6th April 2018) - Hertzog, Jonny; Dias Junior, Antonio Gregorio; Rigby, Rachel E.; Donald, Claire L.; Mayer, Alice; Sezgin, Erdinc; Song, Chaojun; Jin, Boquan; Hublitz, Philip; Eggeling, Christian; Kohl, Alain; Rehwinkel, Jan
Abstract: Zika virus (ZIKV) is a major public health concern in the Americas. We report that ZIKV infection and RNA extracted from ZIKV infected cells potently activated the induction of type I interferons (IFNs). This effect was fully dependent on the mitochondrial antiviral signaling protein (MAVS), implicating RIG‐I‐like receptors (RLRs) as upstream sensors of viral RNA. Indeed, RIG‐I and the related RNA sensor MDA5 contributed to type I IFN induction in response to RNA from infected cells. We found that ZIKV NS5 from a recent Brazilian isolate blocked type I IFN induction downstream of RLRs and also inhibited type I IFN receptor (IFNAR) signaling. We defined the ZIKV NS5 nuclear localization signal and report that NS5 nuclear localization was not required for inhibition of signaling downstream of IFNAR. Mechanistically, NS5 blocked IFNAR signaling by both leading to reduced levels of STAT2 and by blocking phosphorylation of STAT1, two transcription factors activated by type I IFNs. Taken together, our observations suggest that ZIKV infection induces a type I IFN response via RLRs and that ZIKV interferes with this response by blocking signaling downstream of RLRs and IFNAR. Abstract : Hertzog et al. report that ZIKV infection generates RIG‐I and MDA5‐stimulatory RNAs and induces type I interferon (IFN). Viral RNA binds directly to RIG‐I while the viral NS5 protein blocks induction of type I IFN. NS5 also blocks type I IFN signaling by antagonising STAT1 phosphorylation and depletion of STAT2.